Minimally Invasive Ophthalmic Surgery - Fine I, Howard; Mojon, Daniel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Many minimally invasive procedures have been developed over the past decades, leading to a great improvement in eye surgery. This unique textbook and reference guide provides a complete up-to-date overview of minimally invasive surgical techniques in ophthalmology. Lavishly illustrated with superb illustrations and video clips, it presents the state of the art of minimally invasive ophthalmic procedures. It serves as an invaluable resource for all ophthalmic surgeons with widely varying levels of experience, from the resident to the experienced surgeon.
Minimally Invasive Oculoplastic Surgery -- Minimally Invasive Conjunctival Surgery -- Minimally Invasive Lacrimal Surgery -- Minimally Invasive Corneal Surgery -- Descemet's Stripping Endothelial Keratoplasty -- Pterygium -- Minimally Invasive Refractive Surgery -- Minimally Invasive Strabismus Surgery -- Minimally Invasive Iris Surgery -- Minimally Invasive Glaucoma Surgery -- Minimally Penetrating Glaucoma Surgery with the Ex-PRESS™ Miniature Shunt -- New Minimally Invasive, Sclerothalamotomy Ab Interno Surgical Technique -- Glaukos® iStent® Trabecular Micro-Bypass Implant -- Minimally Invasive Cataract Surgery -- Minimally Invasive Vitreoretinal Surgery.
Keywords: Ophthalmology; Ophthalmology